2012
DOI: 10.1002/adma.201200837
|View full text |Cite
|
Sign up to set email alerts
|

A Crown Ether Appended Super Gelator with Multiple Stimulus Responsiveness

Abstract: A crown ether appended super gelator is designed and synthesized. It can gel a variety of organic solvents and shows excellent gelation properties with both low critical gelation concentration and short gelation time. Due to the introduction of the crown ether moiety and a secondary ammonium unit, the supramolecular gels show reversible gel-sol transitions. The supramolecular gels can also be molded into shape-persistent and free-standing objects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 258 publications
(110 citation statements)
references
References 49 publications
2
107
0
1
Order By: Relevance
“…47 Moreover, in diethylene glycol (DEG), Fmoc-F behaves as a common low molecular weight gelator (LMWG), presenting a CGC of 1 wt% (Table S1, ESI ‡). Transparent hydrogels ( Fig.…”
Section: Gelating Ability and Study Of Gel Propertiesmentioning
confidence: 99%
“…47 Moreover, in diethylene glycol (DEG), Fmoc-F behaves as a common low molecular weight gelator (LMWG), presenting a CGC of 1 wt% (Table S1, ESI ‡). Transparent hydrogels ( Fig.…”
Section: Gelating Ability and Study Of Gel Propertiesmentioning
confidence: 99%
“…Subsequently, the same authors reported another example of a supramolecular polymeric gel based on host-guest interactions. [42] Gelator 11 was designed by introduction of a dibenzo-24-crown-8 (DB24C8) crown ether moiety, which acts as the host, and an organic ammonium salt unit, the guest, to a long flexible alkyl chain. The gelator was found to gel a class of organic solvents with a relatively low CGC, and thus falls into the category of supergelators.…”
Section: Mrsgs Based On Host-guest Interactionsmentioning
confidence: 99%
“…其中, 稀土纳米晶因其独特的 4f 电 子能级结构与丰富的能量转换模式, 在高质量发光体、 上转换发光材料、生物荧光探测与标记等领域具有重要 的应用前景 [7~9] . 以聚异丙基丙烯酰胺(PNIPAm)为代表 的温敏聚合物及其水凝胶是一种典型的环境敏感型智 能新材料, 因其在药物分离以及生物工程、化学传感及 形状记忆等方面的潜在应用受到广泛关注 [10,11] . 近年 来, 将荧光纳米晶与智能聚合物进行复合, 制备具有荧 DOI: 10.6023/A12070417 光温敏特性的功能性复合凝胶, 正成为纳米复合新材料 研究中的前沿课题 [12~15] .…”
Section: 引言unclassified